PENGARUH KARAKTERISTIK WIRAUSAHA, MODAL USAHA, SISTEM INFORMASI AKUNTANSI TERHADAP KEBERHASILAN UMKM DESA BANDAR SETIA - Muhammad Alvin Yuzakhri; Hendra Harmain; Yenni Samri Juliati Nasution (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
This study aims to examine the relationship between entrepreneurial characteristics, venture capital, and accounting information systems with the success of micro, small and medium enterprises (MSMEs) in Bandar Setia Village, Percut Sei Tuan District, Deli Serdang Regency. Quantitative methodology was used to validate this research. The sample size for this study was 42 SMEs from Bandar Setia Village, Percut Sei Tuan District, and Deli Serdang Regency. Questionnaires with Likert scale questions were used for this study. Multiple linear regression and the coefficient of determination are used in SPSS 24 to test the hypothesis after the questionnaire is distributed and verified for validity, reliability, and the classical assumptions of normality, multicollinearity, and heteroscedasticity. According to the results of this study, the entrepreneurial mindset can increase the efficiency of small and medium enterprises. shows how having an entrepreneurial bent can help small and medium-sized businesses succeed. Accounting information systems have an effect on the performance of SMEs, as evidenced by research findings, indicating that adopting such systems can enhance organizational success. Data studies reveal that when a company's capital decreases, it has a negative impact on the company's success.